Merawat Alam dan Meningkatkan Spiritualitas: Sinergi Program Penanaman Pohon dan Fasilitas Tempat Baca Al-Qur’an dalam KKN Mandiri Berbasis Ekoteologi di Desa Tolondadu II - Darise, Gina Nurvina; Tuti, Maysaroh Shifah Ash Shafwah; Irwanto, Try Ayunda; Punusingon, Vatma Juliana; Syarief, Agnesya Putri; Sugeha, Luthfia Fitri Utari; Hasan, Tri Putri; Palit, Putri Juwita; Ponongoa, Andina Pratiwi; Lauma, Karina; Lamato, Sayyed Rifki Haekal (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) IAIN Manado, 2025)
The Independent Community Service Program (KKN Mandiri) based on ecotheology is a form of student service to society that integrates environmental awareness with the strengthening of spiritual values. This program was carried out in Tolondadu II Village, Bolaang Uki District, South Bolaang Mongondow Regency, for 45 days with active participation from the community. The main objective was to increase ecological awareness while fostering social harmony through religious-based activities. The method used was Participatory Action Research (PAR), which emphasizes collaboration between students, the community, and local government. The main programs included planting tree seedlings (matoa, agarwood, and avocado) as an environmental conservation effort, as well as providing learning facilities in the form of Qur’an reading stands (rehal) for the children of TPQ Al-Ikhsan. The results showed an increase in children’s motivation to learn the Qur’an, the creation of a more orderly learning environment, and a growing community awareness of the importance of environmental preservation. This program not only provided short-term benefits in terms of facilities and greening but also became a tangible step in fostering a sustainable culture of environmental care and spirituality.